Issues and challenges in managing land inheritance: a study among syarie lawyer in Selangor / Muhammad Adam Farhan Shazari - Shazari, Muhammad Adam Farhan (2022)
The high trend of unclaimed Islamic land inheritance properties has become a protracted and growing issue in the life of the community in Malaysia. Most of the problems of inheritance land management stem from the confusion or scramble of the heirs over the assets as well as the failure of the property owner to manage his property efficiently during his lifetime. The problem of estate management must be addressed immediately to improve the economy of Muslims in various aspects by liquidating and utilizing the value of frozen assets that have not been claimed by the heirs of the deceased for a long time. Therefore, the issues and challenges related to the management of land inheritance property in Islam need to be put to an end. This research has three main objectives namely the first, to understand the concept of inheritance land in Islam. Second, to identify issues and challenges in the management of land inheritance property in Islam and the third is to analyse the best methods in managing Islamic land inheritance. The data obtained in this research is from wholesale interviews that have been conducted online to several syarie lawyers in the state of Selangor. The data that has been analysed is to evaluate and study the problematic factors of Islamic land inheritance management and the best management methods based on the experience of syarie lawyers in solving problems related to Islamic land inheritance property. Therefore, the results of this study can answer all the objectives that I have given to the respondents related to issues and challenges in managing Islamic land inheritance among syarie lawyers in Selangor.